2022
DOI: 10.1111/jerd.12900
|View full text |Cite
|
Sign up to set email alerts
|

Methods to assess tooth gingival thickness and diagnose gingival phenotypes: A systematic review

Abstract: Objective Measurement of the periodontal soft tissue dimension is crucial for clinical decision‐making and aesthetic prognosis. However, the effectiveness of different measuring methods remains unclear. This systematic review aimed to explore the diagnostic accuracy of two non‐invasive methods (namely CBCT and ultrasound) for gingival thickness measurement at different tooth positions. Materials and methods A systematic search was performed using PubMed (including Medline), PubMed Central, OVID, Cochrane Libra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…At the same time, ultrasonic devices provide limited specificity in determining gingival thickness in the posterior sector compared that to in the anterior sector. However, CBCT thickness measurement has proven to be the most reliable method for both anterior and posterior sectors, and future studies should employ this methodology (Wang et al, 2022). Regarding the second point, although the correlation analysis corresponds to an initial estimate, further population‐based studies are required that also control for other covariates such as age and sex, or other environmental variables such as smoking, since the included studies performed a bivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, ultrasonic devices provide limited specificity in determining gingival thickness in the posterior sector compared that to in the anterior sector. However, CBCT thickness measurement has proven to be the most reliable method for both anterior and posterior sectors, and future studies should employ this methodology (Wang et al, 2022). Regarding the second point, although the correlation analysis corresponds to an initial estimate, further population‐based studies are required that also control for other covariates such as age and sex, or other environmental variables such as smoking, since the included studies performed a bivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…11 Recent studies have successfully demonstrated the potential of US in implant dentistry. [12][13][14][15] The diagnostic examination of periodontal and peri-implant phenotypes requires a high level of accuracy. The brightness mode (B-mode) of US devices generates continuous two-dimensional (2D) grayscale images, where brightness is determined by the envelope of the returned echo signal, offering several advantages over conventional methods.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 However, US has difficulty penetrating and accurately imaging dense, calcified structures, such as bone or teeth. To date, only four systematic reviews [12][13][14][15] have focused on the application and validation of US in dentistry, reporting limited findings regarding its accuracy compared to CBCT and probing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a proof-of-concept study, the off-the-shelf deep-learning model is first recruited to segment teeth and bone from CBCT images of Yorkshire pig mandibles, which is then superimposed onto the intraoral scan of the pig semi-automatically. To evaluate the accuracy of this methodology, the gingival thickness obtained from the AI virtual measurements will be compared with those assessed by horizontal transmucosal bone sounding, the current clinical best practice [ 26 ]. Our hypothesis of the current study is that the trained AI models utilized in the current work are mature enough to be applied across subjects without retraining; in addition, a good agreement can be achieved between virtual and clinical measurements of soft tissue thickness.…”
Section: Introductionmentioning
confidence: 99%